Effectiveness of Digital Learning Media on Students' Achievement in Science Education: A Quasi-Experimental Study in Islamic Junior Secondary School - Nurhidayah, Nurhidayah; Syahri, Muhammad; Agus Tinus (Jurnal Pendidikan Fisika, 2025)
The rapid expansion of digital technology compels schools to adopt learning media that elevate achievement and cultivate twenty-first-century competencies. In science education, conventional teacher-centered instruction often fails to sustain engagement or deepen conceptual understanding, creating an urgent need for evidence-based innovations. This study examined the effectiveness of digital learning media in improving science achievement at MTs Muhammadiyah Datarang, an Islamic junior secondary school. A quantitative quasi-experimental design was implemented with two intact classes: an experimental group (n = 27) taught using digital media and a control group (n = 26) taught conventionally. Data were collected via pretest–posttest instruments and analyzed using descriptive statistics, normalized gain (N-Gain), and independent-samples t tests. Results showed that the experimental group attained a mean posttest score of 91.41 and an average N-Gain of 0.70 (high), whereas the control group achieved a score of 80.42 and a N-Gain of 0.27 (low); the difference was statistically significant (p < 0.05). These findings indicate that digital media enhance conceptual understanding, engagement, and motivation compared with traditional instruction. The study’s novelty lies in providing rigorous quantitative evidence from a madrasah context that is underrepresented in the technology-enhanced science learning literature. Integrating interactive, visual, feedback-oriented tools can transform science learning in Islamic schools by enabling deeper processing and more equitable progress. This research contributes to physics education by presenting a practical model aligned with multimedia learning theory, providing classroom benchmark values, and informing teacher development and school-level policy. Future studies should extend the intervention longitudinally, involve larger and more diverse samples, and examine affective and social outcomes to evaluate the sustainability and generalizability of the gains.